Synchronization of Ovulation and Timed Insemination in Lactating Dairy Cattle - Moskáľová L.; Pošivák J. (Folia Veterinaria, 2023)
Successful reproduction of lactating dairy cattle, or in other words its reproductive performance is a limiting factor in the profit ratio of cattle breeding regarding market production. The aim of this research was to evaluate the success rate of synchronization protocols Ovsynch, Presynch/Ovsynch, and Double Ovsynch within the period of 24 months. The success rate of the 1st insemination, 2nd insemination, and after more than 2 inseminations was evaluated. The cattle were of Holstein Friesian breed with a milk yield of 10 200 kg. The animals were sorted into two categories – heifers (protocol Ovsynch) and primiparous, multiparous cows (protocols Presynch/Double Ovsynch). The research proved a 54 % success rate in the category of heifers after the 1st insemination. In the category of primiparous and multiparous cows was the success rate of 41 % after the 1st insemination, 39 % after the 2nd insemination, and 52 % after more than 2 inseminations for the Presynch/Ovsynch protocol. The success rate for Double Ovsynch protocol was 45 % after the 1st insemination, 42 % after the 2nd insemination and 51 % after more than 2 inseminations. The results for the given geographic region of Slovakia exceeded the average.